Strategic ESG Transformation To Enhance Funding Access: A Case Of PT Kilang Pertamina International - Ralang Argi Barus; Erman Sumirat; Sylviana Maya Damayanti (Integrasi Sains Media, 2025)
Environmental, Social, and Governance (ESG) principles are now at the heart of corporate competitiveness and long-term viability. This study assesses PT Kilang Pertamina Internasional's (PT KPI) current ESG practices and identifies areas for improvement that extend beyond regulatory compliance. Using a mixed-methods analysis, the author combined stakeholder analysis, resource-based and gap analyses, and a PESTLE review to assess internal capabilities and external analysis, then benchmarked the results against international standards using the Sustainalytics framework. The study identifies three priority areas for improvement: enhancing waste and water management (Beyond PROPER), revitalizing Process Safety Management (PSM), and strengthening ESG governance structures. These initiatives are expected to reduce operational risks, attract foreign investment, and support long-term financial resilience. Future research could examine how these initiatives influence financial performance, policy outcomes, and stakeholder perceptions.